2009
DOI: 10.1007/s10681-009-9919-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of QTLs associated with salinity tolerance at late growth stage in barley

Abstract: Salinity is a major abiotic stress to barley (Hordum vulgare L.) growth and yield. In the current study, quantitative trait loci (QTL) for yield and physiological components at the late growth stage under salt stress and non-stress environments were determined in barley using a double haploid population derived from a cross between CM72 (salt-tolerant) and Gairdner (salt-sensitive). A total of 30 QTLs for 10 traits, including tiller numbers (TN), plant height, spikes per line (SPL), spikes per plant (SPP), dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
70
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 42 publications
4
70
0
Order By: Relevance
“…The third QTL linked with germination stage tolerance is mapped on chromosome 5H. This QTL is slightly distant from potassium concentration linked QTL reported previously [2] but appears to be very closely located with seed dormancy linked QTL on chromosome 5HC in a population generated from Stirling and Harrington barley varieties [19]. The chromosome 5H QTL may be the same locus associated with seed dormancy in these studies.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The third QTL linked with germination stage tolerance is mapped on chromosome 5H. This QTL is slightly distant from potassium concentration linked QTL reported previously [2] but appears to be very closely located with seed dormancy linked QTL on chromosome 5HC in a population generated from Stirling and Harrington barley varieties [19]. The chromosome 5H QTL may be the same locus associated with seed dormancy in these studies.…”
Section: Discussionsupporting
confidence: 49%
“…However, QTL identified on chromosome 3H at 192.8 cM distance linked with fresh weight per plant in seedling emergence stage salinity stress and at 176.5 cM distance linked with biomass yield in seedling emergence and leaf expansion stages salinity stress is located at different chromosomal region from region linked with sd1/ denso gene in the Baudin x Ac Metcalfe barley DH population at about 55 cM distance [24]. The QTL in the Baudin x Ac Metcalfe DH population is in a very close chromosomal region to two QTL linked with plant height at maturity reported previously in the CM72 x Gairdner DH population in salinity stressed and non-stressed conditions [2]. A semi-dwarf 1 ( sdw1 ) gene on chromosome 3HL control plant height in barley and sequencing of its different alleles locus points to HvGA20ox2 as the functional gene responsible for the phenotype [24, 25].…”
Section: Discussionmentioning
confidence: 98%
“…In barley, many QTLs associated with salt tolerance have been identified [21, 22]. A single locus controlling salt tolerance, HvNax3 , was identified on the short arm of chromosome 7H from a wild barley accession CPI-71284-48, which controls sodium (Na) accumulation in shoots under salt stress [23].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, primer Bmag0125 on chromosome 2H with PIC value 0.567 (Table 3), these markers were sufficient to differentiate all of the genotypes since they generated a high number of allele with high PIC values. The results indicated that this region of chromosome 4H is important for salt tolerance in barley it may be assumed that there is a QTL cluster for salt tolerance in the region of chromosome 4H, and thus the region may be used as an important target for improving salt tolerance of barley Xue et al (2009). The PIC value (0.38) obtained by Pillen et al (2000), who used 22 microsatellite markers and a set of 28 mainly German barley cultivars and two wild forms.…”
Section: Discussionmentioning
confidence: 96%